Counter-terrorism in Ethiopia: manufacturing insecurity, monopolizing speech - Téwodros W. Workneh (Internet Policy Review, 2019)
For nearly three decades, Ethiopia's current ruling party, the Ethiopian People's Revolutionary Democratic Front (EPRDF), has maintained its power through a highly centralized, vanguard party system. Recently, the Ethiopian government has extensively used the provisions of the Ethiopian Anti-Terrorism Proclamation (EATP) to prosecute several Ethiopian citizens and organizations that are critical of the ruling party. By framing the adoption and execution of the EATP as an outcome of EPRDF's long-term hegemonic project coalesced in neopatrimonialism, this paper demonstrates how the Ethiopian State has created a rational-legal bureaucracy that exploits terrorism narratives to stifle critical speech on digital as well as traditional media. The result is the making of an online public that is unsure of what could be considered as a "terrorist" message as opposed to "normal" speech, who, in an attempt to not take the risk altogether, may avoid participating in political discourse. While the disbandment of the neopatrimonial order is key in dislodging Ethiopia's legislative bottlenecks to civic liberties, a more urgent task calls for a move toward participatory, inclusive, and equitable Internet policy framework.
Keywords: 300; Counter-terrorism; Freedom of expression; Ethiopia; Neopatrimonialism; EPRDF